Extensive social intervention: a concept for Social Work (Emancipação, 2026)
The present article introduces the concept of extensive social intervention to methodologically reconceptualize the outreach interventions though street work teams. Street work teams are an important resource for social and health intervention in unconventional contexts in Portugal. They provide services to hard-to-reach populations, those experiencing social exclusion, or those engaging in health-risk behaviours. The purpose of this article is to present and discuss the new concept and the methodologicalprocess of social intervention designated as extensive. Methodologically, the research used a narrative integrative review of the literature. From the literature analysis, the results point to a conceptual framework and the definition of a theoretical-methodological approach that frames extensive social intervention. The conceptual framework presented is grounded in critical social work and triangulates the literature on anti-oppressive practices, the empowerment approach, and the harm reduction perspective. The methodological conceptualization of extensive social intervention systematizes the premises of the intervention, the characteristics of the target populations, and the specific features of the intervention contexts presented in the article. The authors propose the reconceptualization of the street team work as an extensive social intervention. As an implication, the aim is to establish extensive social intervention as a working methodology in social work, thereby contributing to its theoretical and methodological systematization and grounding.
Keywords: Extensive social intervention; outreach interventions; street work; Social Work; anti-oppressive practice; empowerment.